(untitled) (Nexo Revista Científica, 2020)
The purpose of this study is to investigate the factors affecting the employment-oriented empowerment of rural female heads of households in Ilam. In terms of monitoring and degree of control, this is field research and in terms of method of obtaining facts and data processing, it is a survey study and in terms of data collection, it is descriptive-correlational. The statistical population of this study is 14156 rural female heads of households in Ilam. The sample size was set for 374 people using Krejcie and Morgan Table. In this study, due to having a list of the names of all women studied, a systematic sampling method was used. The data collection tool in this study was a researcher-made questionnaire whose face validity and content validity were provided through a panel of experts. The reliability of the questionnaire was also confirmed by Cronbach’s alpha. The results of regression analysis showed that the variables of psychological dimension, social dimension, cultural dimension, and the technical dimension of professional competencies have the greatest impact on the empowerment of rural women and in other words, explain 52% of the changes in the empowerment variable of women.